Three Gd-based magnetic refrigerant materials with high magnetic entropy: From di-nuclearity to hexa-nuclearity to octa-nuclearity - Wang, Minmin; Sun, Chengyuan; Gao, Yujia; Xue, Hong; Huang, Ling; Xie, Yutian; Wang, Jin; Peng, Yuanyuan; Tang, Yanfeng (Frontiers in Chemistry, 2022)
Magnetocaloric effect (MCE) is one of the most promising features of molecular-based magnetic materials. We reported three Gd-based magnetic refrigerant materials, namely, Gd2(L)(NO3)(H2O)‧CH3CN‧H2O (1, H2L = (Z)-N-[(1E)-(2-hydroxy-3-methphenyl)methylidene]pyrazine-2-carbohydrazonic acid), {Gd6(L)6(CO3)2(CH3OH)2(H2O)3Cl}Cl‧4CH3CN (2), and Gd8(L)8(CO3)4(H2O)8‧2H2O (3). Complex 1 contains two GdIII ions linked by two η2:η1:η1:η1:μ2-L2- ligands, which are seven-coordinated in a capped trigonal prism, and complex 2 possesses six GdIII ions, contributing to a triangular prism configuration. For complex 3, eight GdIII ions form a distorted cube arrangement. Moreover, the large values of magnetic entropy in the three complexes prove to be excellent candidates as cryogenic magnetic coolants.